Transformasi Pola Konsumsi Rumah Tangga Santri terhadap Produk Digital Ekonomi Syariah pada Masa Pembatasan Sosial Covid-19 - Eni Susilowati; Siti Anasatul Nur Alifah; Endira May Susanti (SINDA: Comprehensive Journal of Islamic Social Studies, 2021)
The COVID-19 pandemic and social distancing policies have triggered significant changes in the household consumption patterns of Islamic boarding school students (pesantren). This study aims to analyze the transformation of Islamic boarding school household consumption patterns towards digital Islamic economic products and the factors influencing their acceptance during the social restrictions period. The study used a qualitative approach with a case study at the Nurul Iman Islamic Boarding School in Blitar City. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using reduction, presentation, and conclusion-drawing techniques. The results show that limited mobility has accelerated the use of halal marketplaces, Islamic digital wallets, and digital Islamic banking services. This transformation is adaptive and pragmatic, yet remains grounded in Sharia compliance. The research findings confirm that the Islamic digital economy has high adaptability and has the potential to strengthen the resilience and economic independence of Islamic boarding school households in a sustainable manner